TAX AMNESTY DALAM PRESPEKTIF UMKM UD. BUNGA DI JAWA TIMUR - Rachel Laurenzia Liandoro; Sujoko Efferin (Perpustakaan Universitas Surabaya, 2018)
This study aims to provide knowledge about the system of taxation by companies, especially SMEs to run the system of taxation routine and Tax Amnesty. In this research explains that every Taxpayer has the same obligation in doing taxation according to its business activity. However, there are still many taxpayers who have not done their duties so that thegovernment implements Tax Amnesty to resolve the issue because it can harm the state. Implementation of Tax Amnesty got positive and negative impression especially from UMKM. Some Taxpayers follow Tax Amnesty is not even based on self-awareness but from the existence of several factors that affect. With the Tax Amnesty of Taxpayers, especially UMKM hopes that Tax Amnesty can promote and improve the state economy and make the practice of taxation better, transparent, and evenly in all levels of society.